ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CASHLESS SOCIETY - Wulandari, Ayu; Kustina, Lisa; Nurastuti, Preatmi (Jurnal Investasi, 2023)
This research is motivated by the increasingly widespread use of electronic money as payment transactions in order to reduce the use of paper money to create a cashless society. This type of research is quantitative research with secondary data in the form of time series which includes electronic money transaction data, electronic money circulating data, means of payment by card, and electronic money infrastructure data obtained from Bank Indonesia's official website for 2018-2022. The results of the study show that electronic money transactions have an effect on a cashless society, electronic money in circulation has an effect on a cashless society, digitalization of electronic money has an effect on a cashless society, electronic money infrastructure has an effect on a cashless society, electronic money infrastructure can strengthen electronic money transactions on a cashless society, money infrastructure electronic money is able to strengthen the circulation of electronic money towards a cashless society, and electronic money infrastructure is able to strengthen the digitalization of electronic money towards a cashless society.